Elevated Circulating Fetuin-B Levels Are Associated with Insulin Resistance and Reduced by GLP-1RA in Newly Diagnosed PCOS Women - Mani Mokou; Shan Yang; Bin Zhan; Shan Geng; Kejia Li; Mengliu Yang; Gangyi Yang; Wuquan Deng; Hua Liu; Dongfang Liu; Zhiming Zhu; Ling Li (Hindawi Limited, 2020)
Background. Previous studies have suggested that Fetuin-B seems to be a secreted adipokine related to metabolic diseases. However, the results have been inconsistent. Here, our objective is to investigate the changes in circulating Fetuin-B levels in women with polycystic ovary syndrome (PCOS) and analyze the association of Fetuin-B and insulin resistance (IR). Methods. The current study is comprised of a cross-sectional study and a series of interventional studies. Oral glucose tolerance test (OGTT) and euglycemic-hyperinsulinemic clamp (EHC) were engaged to assess glucose tolerance and insulin sensitivity. Serum Fetuin-B levels were determined by ELISA. Results. Serum Fetuin-B and TNF-α levels were markedly increased in women with PCOS compared to healthy women. Circulating Fetuin-B was positively associated with body mass index, waist-to-hip ratio, the percentage of body fat (FAT%), systolic blood pressure, triglyceride, low-density lipoprotein cholesterol, fasting blood glucose, 2 h blood glucose after glucose overload, fasting insulin, 2 h insulin after glucose overload, HOMA-insulin resistance index (HOMA-IR), the area under the curve for insulin (AUCi), AUCg, and TNF-α, while negatively associated with M value and follicular stimulating hormone (FSH). During the EHC, Fetuin-B levels were found to be significantly increased in PCOS women. After a glucose challenge, serum Fetuin-B levels in healthy women were significantly increased. Lipid infusion reduced serum Fetuin-B levels in 30 healthy subjects. After six months of glucagon-like peptide-1 receptor agonist (GLP-1RA) intervention, serum Fetuin-B concentrations in PCOS women markedly decreased following ameliorated IR. Conclusion. Our results indicate that Fetuin-B may be a biomarker of IR in individuals with PCOS. This trial is registered with ChiCTR-IIR-16007901.